Second Language Learners’ Pauses Over Different Times Intervals in L2 Writing Essays: Evidence From a Keystroke Logging Program - Мохаммед Мохсен (Психолінгвістика)
Purpose. Several studies have been conducted to analyse students’ pauses during first language and/or second language writing to indicate the magnitude of the underlying cognitive processes learners have. Majority of studies have examined students’ pauses at a threshold 200ms. However, little is known about recording second language learners' pauses at different pauses’ times over different types of genres. The current investigation reports a case study of L2 learners’ cognitive processes by recording their pauses (<500ms, <1000ms, and <2000ms) during L2 writing in response to multiple genres prompts.